Abuses and Distortions in Emotional Processes as Risk Factors for Parricide - Grattagliano, Ignazio; Greco, Romy; Vella, Giancarlo Di; Corbi, Grazia Maria; Campobasso, Carlo Pietro; Romanelli, Maria Carolina; Ostuni, Alessio; Petruzzelli, Nicola; Brunetti, Valeria; Cassibba, Rosalinda (International Journal of Criminology and Sociology, 2015)
Parricide is a rare case of murder having a strong emotional impact on public opinion, especially when it is heinous and perpetrated by minors. Based on the analysis of the judicial files archived at the Minor Penal Institute "N. Fornelli" of Bari, the authors will report three impressive cases perpetrated by minors, by focusing on their emotional features. Differences between the crimes of parricide committed by adults and minors will be highlighted, by analyzing the peculiar relations between the problems underlying parricide and the role played by abuses and maltreatments experienced by minors perpetrating such crime. In particular, attention will be paid to the emotional processes aroused in minor parricide offenders.